Epigenomics and Transcriptomics in the Prediction and Diagnosis of Childhood Asthma: Are We There Yet? - Forno, Erick; Celedón, Juan C. (Frontiers in Pediatrics, 2019)
Asthma is the most common non-communicable chronic disease of childhood. Despite its high prevalence, to date we lack methods that are both efficient and accurate in diagnosing asthma. Most traditional approaches have been based on garnering clinical evidence, such as risk factors and exposures. Given the high heritability of asthma, more recent approaches have looked at genetic polymorphisms as potential “risk factors”. However, genetic variants explain only a small proportion of asthma risk, and have been less than optimal at predicting risk for individual subjects. Epigenomic studies offer significant advantages over previous approaches. Epigenetic regulation is highly tissue-specific, and can induce both short- and long-term changes in gene expression. Such changes can start in utero, can vary throughout the life span, and in some instances can be passed on from one generation to another. Most importantly, the epigenome can be modified by environmental factors and exposures, and thus epigenetic and transcriptomic profiling may yield the most accurate risk estimates for a given patient by incorporating environmental (and treatment) effects throughout the lifespan. Here we will review the most recent advances in the use of epigenetic and transcriptomic analysis for the early diagnosis of asthma and atopy, as well as challenges and future directions in the field as it moves forward. We will particularly focus on DNA methylation, the most studied mechanism of epigenetic regulation.